Characterization of Structure and Dynamics of the Guanidine‐II Riboswitch from Escherichia coli by NMR Spectroscopy and Small‐Angle X‐ray Scattering (SAXS). (9th December 2021) - Schamber, Tatjana; Binas, Oliver; Schlundt, Andreas; Wacker, Anna; Schwalbe, Harald
Abstract: Riboswitches are regulatory RNA elements that undergo functionally important allosteric conformational switching upon binding of specific ligands. The here investigated guanidine‐II riboswitch binds the small cation, guanidinium, and forms a kissing loop‐loop interaction between its P1 and P2 hairpins. We investigated the structural changes to support previous studies regarding the binding mechanism. Using NMR spectroscopy, we confirmed the structure as observed in crystal structures and we characterized the kissing loop interaction upon addition of Mg 2+ and ligand for the riboswitch aptamer from Escherichia coli . We further investigated closely related mutant constructs providing further insight into functional differences between the two (different) hairpins P1 and P2. Formation of intermolecular interactions were probed by small‐angle X‐ray scattering (SAXS) and NMR DOSY data. All data are consistent and show the formation of oligomeric states of the riboswitch induced by Mg 2+ and ligand binding. Abstract : Gdn‐II riboswitch aptamer from E. coli with wild‐type and loop‐mutated constructs were investigated in the context of ligand interactions. Based on NMR spectroscopy and small‐angle X‐ray scattering (SAXS) data, previous crystal structures were confirmed, and an intermolecular ligand binding mechanism with the P1 loop as interaction interface instead of the postulated (intramolecular) P1‐P2 kissing loop was found.